Hyponatraemia and confusion in a 70-year-old female when bupropion was added to dothiepin and escitalopram. (October 2015) - Wiggins, Aaron; Balasubramanian, Thangam; Ferraro, Angelo
Objective: Hyponatraemia secondary to syndrome of inappropriate antidiuretic hormone secretion (SIADH) is a well-recorded adverse event observed in elderly patients on antidepressant treatment. Bupropion is an antidepressant agent usually reserved as an augmentation strategy for treatment-resistant depression. While hyponatraemia is not a documented side effect of bupropion, there are a few cases outside of Australia reported in the literature. We report on a case of hyponatraemia observed on bupropion initiation in a 70-year-old female patient with treatment-resistant depression. We present a discussion of the possible mechanism of action for the hyponatraemia observed in our case and prior reported cases. Conclusions: Our case and review of the available literature highlights the dangers of polypharmacy in the management of treatment-resistant depression. Our findings suggest that the association of hyponatraemia with bupropion in our and subsequent cases was likely the result of medication interaction and not a direct side effect of bupropion. Where bupropion is being used as an augmenting agent in the treatment of depression we would suggest checking of serum sodium prior to commencement of bupropion, and monitoring thereafter. This is especially important in elderly patients where other risk factors for hyponatraemia are likely to be present.